PENDAPATAN PEMBUDIDAYA IKAN ANGGOTA KELOMPOK WIRAUSAHA PEMUDA DAN IMPLIKASINYA TERHADAP KETAHANAN EKONOMI KELUARGA (Studi di Kelompok Wirausaha Pemuda Kota Palangka Raya Provinsi Kalimantan Tengah) - , FANNY KARTIKA OKTAVIANTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Youth Entrepreneurship Group (YEG) is one of the programs of the Ministry of Youth and Sports. The goal of this program is to foster the entrepreneurial spirit among youths and to reduce unemployment. This research is aimed to analyze factors that affect fish-farming using fishpond and keramba (basket on water for growing fish), to calculate and analyze the amount of revenue of grous and individual, and determine the implication of the revenue towards family economic resilience which is managed by Youth Entrepreneurship Group in Palangka Raya City, Central Borneo Province. This research used descriptive qualitative method by structured interviews, observation and literature study. Study of revenue and revenue is used to measure the revenue of fish-farmers in Youth Entrepreneurship Group. In addition, to measure the family economic resilience which indicated by individual poverty status, the standard of Palangka Rayaâs Minimum Wage. In 2013 the minimum wage in Palangka Raya City is IDR 1.676.058. The research has some results. They are, first, the factors that affect amount of YEG revenue are the differences of given capital, experience fish farming, and the fishing mortality rate. Second, the average of revenue contribution of fish farming are 56 percent and based on the revenue analysis using the standard of Palangka Rayaâs Minimum Wage, the members of YEG which categorized poor and non-poor are balance (15 people) or 50 percent. The activity of fish farming uses fishpond and keramba leads the YEG members to increase their revenue and sufficient their economic life, as well as increasing the family economic resilience of the members.